The Optimizing Intraoperative Nursing Care: Hypothermia Management in Exploratory Laparotomy for Adhesiolysis and Jejunal Diverticulectomy - Alfarizi, Muhammad (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Exploratory laparotomy surgery is a procedure that is often found in patients with adhesive obstruction ileus. In the intraoperative phase, exploratory laparotomy takes a long time and exposure to cold environments and anesthetic drugs often causes hypothermia which has an impact on serious complications. The purpose of this study was to analyze intraoperative hypothermia management interventions in patients undergoing exploratory laparotomy surgery with adhesiolysis and jejunal diverticulectomy. The study design used a case study with a nursing care approach. The research sample was Mr. S with a diagnosis of adhesive obstruction ileus taken using the convenience sampling technique. Data collection was carried out by observation during surgery and documentation studies with a perioperative nursing care format. Hypothermia management was carried out by providing warm irrigation interventions of the gastrointestinal organs with 0.9% NaCl fluid at a temperature of 380C and laparotomy gauze when starting exploration for 4 hours according to the duration of surgery. The results of the study showed significant clinical improvements in body temperature, skin, blood pressure, pulse and gastrointestinal motility. The irrigation method with warm NaCl 0.9% during exploratory laparotomy is very effective in overcoming intraoperative hypothermia and facilitating the adhesiolysis process in the gastrointestinal organs.